Waqf Awareness for Majelis Taklim and Muslimah Organizations - Soediro, Achmad; Kusumawardani, Media; Farhan, Muhammad; Adhitama, Fardinant; Kesuma, Nilam (Sricommerce: Journal of Sriwijaya Community Services, 2023)
The implementation of community service with the theme "Waqf Awareness for the Board of Taklim Council and Muslimah Organizations in South Sumatra" was carried out at the end of October 2022. This activity was responded well by the participants. This can be seen by the number of qualified questions submitted. This service program was attended by 77 main participants who were members and administrators of Muslim women's organizations as well as waqf activists, and added 153 participants from Sharia Accounting students who were included to add to their insights about Islamic economics and finance. The good response regarding community service activities is broadly divided into at least two things: first, this activity is able to increase the participants' knowledge and; the presenters explained the material presented well.